Biological Adhesion - Brubaker, C. E.; Messersmith, P. B.; S. N., Aqida (Elsevier, 2016)
This chapter describes strategies used in the biological world for adhesion to surfaces under a variety of environmental conditions. The fibrillar attachment systems of geckos and other organisms are representative of strategies operative in dry environments, whereas the adhesive glues secreted by mussels, barnacles, algae, and sandcastle worms are characteristic of wet biological adhesives. Biomimetic polymer strategies motivated by biological adhesives are illustrated, including novel polymer systems that mimic both dry and wet types of biological adhesives. The goal of these efforts is to capture the salient properties of the native systems in synthetic versions intended for consumer, industrial, military, and medical use.